Copyright in the Information Age: Librarian’s Viewpoint - T.B., Anand; B., Raveendra Reddy (DESIDOC Journal of Library & Information Technology, 2003)
The intellectual work music be produced and it must be accessible. The copyright act attempted to balance the rights of authors to benefit from their writing and stimulate creativity and needs of the readers to have ready access to information. This article explains international Copyright Law and Indian law of copyright briefly. It also describes copyrightable items and reasons for infringement of copyright. http://dx.doi.org/10.14429/dbit.16.6.3289